Digital Marketing Tanaman Hias dan Sayuran Hasil Urban Farming pada Masa Pandemi Covid-19 - Doni Sahat Tua Manalu; Ade Astri Muliasari; Hidayati Fatchur R; Faranita Ratih L (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2022)
One thing that has changed due to the Covid-19 pandemic is the increasing public interest in farming, especially in urban areas (urban farming). The purpose of writing the results of the implementation of community service in an effort to socialize digital marketing of ornamental plants and vegetables from urban farming during the pandemic Covid-19. The method that has been chosen as the location of the service is done intentionally (purposive). The results obtained are many digital marketing platforms that can be used easily by participants and are supported by the increasing number of internet users in Indonesia so that the use of digital marketing as a marketing of urban farming crops is very possible. The data obtained that the purpose of the participants to grow vegetables and ornamental plants produced using the urban farming method is mostly to increase household income and consumption, then 100% of the participants stated that the activities of Lecturers in Service in Cihideung Ilir Village are able to increase knowledge and are important for participants.